Portfolio as an assessment tool in selected Malaysian English as a Second Langauge secondary classrooms - Swaran Singh, Charanjit Kaur (2014)
This study investigated the implementation of portfolio as an assessment tool for learning in selected Malaysian ESL (English as a Second Language) secondary classrooms. It was also conducted with the intention of constructing a model of portfolio assessment for ESL teachers to integrate assessment with teaching. It also investigated students’ response towardsthe use of portfolio as an assessment tool on learning and factors that influenced ESL teachers to use portfolio as an assessmenttool. Qualitative approach specifically, a case study was employed so that a detailed information could be obtained from the teachers’ experiences in the natural context of implementing portfolio as an assessment tool. Data collected through interviews, observations and documents were analysed inductively using the data analysis approach expounded by Miles and Huberman (1994). Data from interviews, observations and documents were analysed inductively for dominant issues and categories. The portfolio assessment was implemented at the beginning of the year in January, in two different schools in an ESL class of 35-40 students in Perak and Selangor. The participants consisted of nine ESL teachers and forty-five ESL students, who come from a variety of different linguistic and cultural backgrounds, in a Malaysian classroom setting. The nine ESL teachers were interviewed. The students were also interviewed in groups to ascertain their response towards the use of portfolio as an assessment tool. Each interview lasted between an hour to about two hours, were tapes recorded, transcribed verbatim and analysed manually. Observations were made to investigate the teachers’ implementation of portfolio as an assessment tool. The model was developed based on the teachers’ pedagogical practices. Triangulation method was used to interpret the data and the findings showed that the overall content of the portfolios can be used to validate and document both process and product of learning and formation of language. The findings showed that the teachers followed a general procedure for implementing portfolio as an assessment tool which included: explaining the assessment purpose, evaluating the portfolio and preparing the teaching and learning activities. The findings also revealed that there were five major considerations in implementing portfolio as an assessment tool, namely assessment purpose, collection of evidence, evaluation of evidence, reflecting on learning and assessment decision. Teachers adhered to these stages to ensure the implementation of portfolio as an assessment tool work smoothly. It was also found that the implementation of portfolio as an assessment tool in the classroom has allowed the teachers to evaluate their students’ potential in tracking the ability to master the topics taught and enable students to know how they progressin their lessons. The findings also indicated that the students noticed the potential of using portfolios thatcould improve their learning because it enabled students to think critically and independently. Four major conclusions were drawn from this study. First, teachers, who implemented portfolio as an assessment tool, sustain their teaching to ensure accuracy of the assessment techniques, improve their satisfaction in evaluation, and ultimately benefit the ESL students. Second, portfolio assessment model allows the teachers to see new developments and directions in teaching and learning if it is implemented appropriately. Third, addressingthe issue that students study merely for the examination can reduce the stress for the stakeholders involved and integrate portfolio and traditional assessment complementarily can make evaluation practical. Finally, portfolio assessment processes are in line with the social constructivist view of learning which promotes learners to create their personal meaning from any learning situation or social context without relying too much on the teachers. The study has provided several pedagogical implications for adopting portfolio as an assessment tool in the ESL classrooms for instruction, assessment and curriculum to ESL teachers, policy makers and educational researchers in the Malaysian and other similar contexts. Recommendations have also been made for the benefits of ESL teachers and future researchers more broadly.